An Integrative Islamic Education Framework Based on the Qur'an, Sunnah, Sirah, and Maqasid al-Shariah at PKBM Jabal Dau Center Malang - Delta Novita Putri (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2026)
Islamic education requires a holistic approach that integrates normative religious foundations with contextual learning and character development to address contemporary educational challenges. Although previous studies have examined the Qur'an, Sunnah, Sirah Nabawiyah, and Maqasid al-Shariah individually, limited attention has been given to their integrated implementation in non-formal Islamic education, particularly for orphaned and underprivileged students. This study aimed to explore how these four Islamic foundations were implemented at PKBM Jabal Dau Center Malang and to examine their contribution to educational quality and students' character development. A qualitative case study design was employed. Data were collected through in-depth interviews with the school principal, an Islamic Religious Education teacher, and two students, complemented by classroom observations and document analysis conducted between November and December 2025. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the Qur'an and Sunnah serve as the normative foundation of curriculum and instructional practices, Sirah Nabawiyah provides contextual moral exemplars, and Maqasid al-Shariah is operationalized through ten character indicators supported by a gamification-based learning system. This integrated approach enhances students' religious commitment, discipline, critical thinking, social responsibility, and ethical behavior. The study contributes a holistic conceptual framework and an adaptable character education model for strengthening educational quality in non-formal Islamic institutions serving vulnerable learners.